Preparation of Amino Modified Coal Gangue and its Adsorption of Pb (II) - Bojun LIU; Suling YAO; Xianshu DONG; Yuanpeng FU (Kuangchan zonghe liyong)
The development of coal gangue adsorbent can not only effectively utilize it, but also reduce the treatment cost of heavy metal ion wastewater. A series of adsorbent materials were prepared by intercalation, hydrochloric acid pretreatment and amino modification using coal gangue from JinnengTashan Coal Preparation Plant as raw materials. The experimental conditions were optimized by Box-Behnken experimental design method. The adsorption properties of Pb ( II ) in water were investigated. The physical and chemical properties of the adsorption materials were analyzed by XRD, FTIR, BET and Zeta potential. The results showed that the adsorption capacity of Pb ( II ) by coal gangue after intercalation, hydrochloric acid pretreatment and amino modification was increased from 1.89 mg/g of the raw ore to 23.02 mg/g. The grafting rate of amino groups on the surface of coal gangue is the key to adsorption performance. The adsorption of Pb ( II ) by the adsorbent conforms to the pseudo-second-order kinetic model, and the isothermal adsorption conforms to the Langmuir adsorption model. The amino-modified coal gangue prepared from coal gangue has the advantages of low cost, good adsorption performance, and potential industrial application value.